Efficacy of Integrated Traditional Chinese and Western Medicine for Treating COVID-19: A Systematic Review and Meta-Analysis of RCTs - Bei Yin; Bei Yin; Yi-Ming Bi; Yi-Ming Bi; Lu Sun; Lu Sun; Lu Sun; Jin-Zhu Huang; Jin-Zhu Huang; Jia Zhao; Jia Zhao; Jia Yao; et al. (Frontiers Media S.A., 2021)
Background: Integrated Chinese and Western medicine (integrated medicine) is routinely used in the treatment of coronavirus disease 2019 (COVID-19) in China. In this study, we undertook a systematic review and meta-analysis of published randomized controlled trials (RCTs) to evaluate the efficacy of integrated medicine therapy for patients with COVID-19.Methods: In this meta-analysis, we searched PubMed, Embase, Web of Science, SinoMed, China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), and Wanfang databases from inception to April 12, 2021, to identify RCTs of integrated medicine in the treatment of COVID-19. The quality of RCTs was assessed by the Cochrane risk of bias tool. RevMan v5.3 and Stata software packages were used for statistical analysis.Results: Nineteen RCTs involving 1,853 patients met our inclusion criteria. Compared with patients treated by conventional Western medicine (CWM), patients treated by integrated medicine have a higher overall effective rate [RR = 1.17, 95% CI: (1.10, 1.26), p < 0.00001], fever disappearance rate [RR = 1.25, 95% CI: (1.04, 1.50), p = 0.02], fatigue disappearance rate [RR = 1.28, 95% CI: (1.00, 1.63), p = 0.05], and chest CT improvement rate [RR = 1.24, 95% CI: (1.14, 1.34), p < 00001]. Beneficial effects of the integrated medicine therapy were also seen in C-reactive protein (CRP) level [WMD = −4.14, 95% CI: (−6.38, −1.91), p = 0.0003] and white blood cell (WBC) count [WMD = 0.35, 95% CI: (0.11, 0.58), p = 0.004]. Subgroup analyses showed that, when the treatment time is <2 weeks, the effect of integrated medicine treatment is more obvious in improving the overall effective rate, clinical symptoms (fever, fatigue, and cough), the CRP level, and WBC count compared with that of the CWM treatment. For patients with severe and non-severe COVID-19, integrated medicine is more effective in improving fever and cough symptoms and WBC count than using CWM alone.Conclusion: The results of the current meta-analysis suggested that the integrated medicine can improve the clinical symptoms, chest CT and infection indicators of COVID-19 patients. Even if the treatment time is <2 weeks, the effect of integrated medicine in improving symptoms is more obvious compared with the treatment of CWM. However, the results should be interpreted cautiously due to the heterogeneity among the studies.